Germination ecology of Rhynchosia capitata: an emerging summer weed in Asia - Ali,H.H. (2013)
Rhynchosia capitata is becoming an increasing problem in summer crops, such as cotton, soybean, pearl millet and mungbean in many Asian countries. Laboratory and greenhouse studies have been conducted to determine the effects of several environmental factors on seed germination patterns and seedling emergence of R. capitata. We investigated whether the diverse ecological factors such as temperature, light, salinity, moisture stress, pH, and soil depth affected germination and seedling emergence of R. capitata. Germination increased as temperature increased from 25ºC and significantly reduced at 45ºC. Presence or absence of light did not influence germination. Germination of R. capitata was sensitive to increased salt and moisture stress, as well as to seed burial depth. Only 48% of seeds germinated at 150 mM salt concentration compared to 100% in control (distilled water). Similarly, 15% of seeds germinated at an osmotic potential of ‑0.8 MPa compared to 88% at ‑0.2 MPa. The optimum pH for seed germination of R. capitata was 7 (98% germination), but the seeds also germinated at lower level of pH 5 (85%) and at higher level of pH 10 (75%). In seed burial trial, maximum seedling emergence of 93% occurred at 2 cm depth, and seedling did not emerge from a depth of 12 cm. The high germination ability of R. capitata under a wide range of ecological factors suggests that this species is likely to be the one to cause more problems in a near future, if not managed appropriately.